A “Hybrid” Sural Flap for Treatment of Chronic Calcaneal Osteomyelitis - Wang, Chun-Yang; Sun, Lu-Yuan; Chai, Yi-Min; Han, Pei; Wen, Gen; Chen, Hua (Journal of Reconstructive Microsurgery, 2014)
Background The treatment of chronic calcaneal osteomyelitis remains a challenge for orthopedic and plastic surgeons. The basis of surgical therapy includes thorough debridement of infected tissue and reconstruction with well-vascularized flaps.Methods A “hybrid” sural flap composed of an adiponeurofascial flap proximally and a neurofasciocutaneous flap distally is described here. The adiponeurofascial flap was used to obliterate the bone cavity, and the distal part was used to resurface soft tissue defects. Five patients with chronic calcaneal osteomyelitis were treated with this modified sural flap.Results The size of the adiponeurofascial flap ranged from 5.0 × 4.0 cm to 13.0 × 5.0 cm, and that of the neurofasciocutaneous flap ranged from 6.5 × 3.0 cm to 6.0 × 8.0 cm. The donor defects were covered with skin grafts in three patients and closed primarily in two patients. All the flaps survived completely without any complications, the skin graft and the skin over the adiponeurofascial flap healed uneventfully. There was no evidence of recurrent infection during the follow-up period.Conclusion The modified “hybrid” sural flap is simple and reliable and is a good candidate for treatment of chronic calcaneal osteomyelitis.
Keywords: calcaneal osteomyelitis; sural flap; adiponeurofascial flap; neurofasciocutaneous flap